Measurement of Environmental Awareness of University of Technology Students towards some Environmental Statements - Azhar M. Haleem; Daliah M. Hassan (Engineering and Technology Journal, 2016)
Environmental awareness level for university of technology students was investigated at scholastic year (2013-2014) towards some environmental statements suggested by the researcher and endorsed by ten of local environmental experts. 341 students were selected by using random selection technique divided into (176) male and (165) female belong to different scientific departments and different stream. Questionnaire form was designed, included 30 questions distributed at three contents, pollution, environmental awareness and environmental conservation, ten questions for each topic, Likert quaternary scale with known weight was used. All findings were analyzed by descriptive analysis, T test and variable analyses (ANOVA I). From the results, we note environmental awareness towards environmental status among students of university (72.1%) Compared with the supposed ratio (70%), there is no significant differences according to gender variable.